Gaseous [CnH2n+1+ ... 1,3-diphenylpropane] Ion/neutral complexes containing alkyl cations of different acidities and hydride Ion affinities - Matthias, Carsten (Array, 2009)
Summary: Gaseous ion/neutral (I/N) complexes [R+ ... C6H5CH2CH2CH2C6H5] with R = t-C4H9+, s-C4H9+ and s-C3H7+ have been generated by protonation of the corresponding precursor compounds, R-C6H4CH2CH2CH2C6H5, in the chemical ionisation (CI) source of a sector-field mass spectrometer. The fragmentation of these I/N complexes and several deuterium-labelled isotopologues on the metastable ions’ timescale (20−30 μs), as studied by MIKE spectrometry, revealed that (i) the initial ring position (meta- or para-) of R = t-C4H9+ does not affect their intra-complex reactivity, (ii) the fragmentation of the s-C3H7+ and s-C4H9+ ions is dominated by proton transfer to the 1,3-diphenylpropane neutral but hydride ion abstraction in the reverse direction competes to a minor extent, (iii) the secondary alkyl cations exhibit the same regioselectivity (kα-H/kω-H = 1.0) and kinetic isotope effect (kH/kD = 1.6) in the hydride transfer channel as do tertiary alkyl cations, (iv) the s-C4H9+ ions do not undergo skeletal isomerisation